Rescheduling Proyek Pembangunan Jembatan Palu V Menggunakan Microsoft Project - Aslam, Aslam; Kamaludin, T.M. (Civil Engineering Department, Tadulako University, 2021)
One form of project planning is Project scheduling. Project scheduling is one of the elements of Project planning results, which can provide information on the relationship of each other activity to the entire project, the identification of relationships that must be precedence between activities, showing realistic cost and time estimates for each activity on project completion. In this research the author plans to process project work activity of the Palu V Bridge development by limiting its job stage to the quality of concrete work of FC ' 30MPa for the building over the floor plate. This type of research is analytic. Data collection in the form of secondary data such as schedule and RAB is done by requesting directly the required data to the relevant party. Then conducted initial schedule evaluation, followed by using Microsoft Project 2019 tool as processing result of the project Process Bridge Hammer V. From the results of the study it was concluded that process use Microsoft Project 2019 requiring a duration of 199 working days. While the scheduling is carried out in the field, the executor requires a duration of 366 working days and the planned scheduling of the implementing party takes 167 working days. If compared to the results of scheduling time duration with the implementation of the field and the duration of the execution planner, the results obtained by the researcher more than 167 days from the time of implementation in the field and slower 32 days from the duration of the planning time.